Safety of AS03-adjuvanted influenza vaccines: A review of the evidence. Issue 23 (21st May 2019) - Cohet, Catherine; van der Most, Robbert; Bauchau, Vincent; Bekkat-Berkani, Rafik; Doherty, T. Mark; Schuind, Anne; Tavares Da Silva, Fernanda; Rappuoli, Rino; Garçon, Nathalie; Innis, Bruce L.
Highlights: Non-clinical studies raised no safety concerns regarding the use of AS03. In clinical trials, AS03-adjuvanted influenza vaccines were generally well tolerated. Post-licensure data showed a favourable benefit-risk profile in various populations. The increased risk of narcolepsy with Pandemrix may not be directly linked to AS03. Available safety data support the development and use of AS03-adjuvanted vaccines. Abstract: Clinical and post-licensure data have demonstrated that AS03-adjuvanted inactivated split virion vaccines, many with reduced antigen content, are effective against influenza infection. The objective of this review is to provide a comprehensive assessment of the safety of trivalent seasonal, monovalent pre-pandemic and pandemic AS03-adjuvanted influenza vaccines, based on non-clinical, clinical and post-licensure data in various populations. Non-clinical studies on local tolerance, toxicology and safety pharmacology did not raise any safety concerns with AS03 administered alone or combined with various influenza antigens. Data from clinical trials with over 55, 000 vaccinated subjects showed that AS03-adjuvanted influenza vaccines were generally well tolerated and displayed an acceptable safety profile, although the power to detect rare events was limited. Approximately 90 million doses of A/H1N1pdm09 pandemic influenza vaccines ( Pandemrix and Arepanrix H1N1) were administered worldwide, which contributed post-licensure data to the collective safety data for AS03-adjuvanted influenza vaccines. An association between Pandemrix and narcolepsy was observed during the A/H1N1pdm09 pandemic, for which a role of a CD4 T cell mimicry sequence in the haemagglutinin protein of A/H1N1pdm09 cannot be excluded. Provided that future AS03-adjuvanted influenza vaccines do not contain this putative mimicry sequence, this extensive safety experience supports the further development and use of AS03-adjuvanted inactivated split virion candidate vaccines against seasonal and pandemic influenza infections.